OP0166 Antibodies Against Periodontal Pathogens are not Associated with Joint Swelling or Autoimmunity Associated with RA in a Cohort of Healthy Individuals at Increased Risk of Rheumatoid Arthritis. (9th June 2015) - Finckh, A.; Mueller, R.B.; Dudler, J.; Moeller, B.; Kyburz, D.; Walker, U.; Von Muehlenen, I.; Bas, S.; Gabay, C.; Bostanci, N.
Abstract : Background: Evidence suggests an association between periodontitis and rheumatoid arthritis (RA). If the association between the two diseases is causal, an immune response against common pathogenic bacteria involved in periodontitis should precede the development of the disease. It is unknown whether periodontitis is associated with early symptoms of the disease in healthy individuals at increased risk of developing RA. Objectives: To examine if serum antibodies against pathogenic bacteria involved in periodontitis are associated with early symptoms of the disease in healthy individuals at increased risk of developing RA. Methods: This is a nested case-control study of a prospective cohort of first degree relatives of patients with RA (FDRs). FDRs had no established rheumatologic condition at inclusion. All FDRs provide serum at inclusion and are followed prospectively until development of RA. We selected 4 groups of patients, corresponding to different phases of RA disease development (1): Group 1 - FDRs at risk of RA without signs and symptoms of arthritis and no systemic autoimmunity (control group); Group 2 – FDRs with systemic autoimmunity associated with RA (anti-CCP+ or rheumatoid factor+); Group 3 - FDRs with inflammatory arthralgias without clinical arthritis; Group 4 - FDRs who have presented at least one swollen joint ("Unclassified arthritis"). The four groups were matched for tobacco smoking, age, sex and shared epitope status using propensity scores. The primary outcome was the levels of serum immunoglobulin (Ig) G against five selected periodontal pathogens Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, Aggregatibacter actinomycetemcomitans and Prevotella intermedia and one commensal oral species ( Streptococcus oralis ) assessed using validated enzyme-linked immunosorbent assays. We also normalized the absolute levels of IgG against the pathogens using the IgG level against the commensal S.oralis (ratio). Non linear ANCOVA models were fit to test the association between levels of IgGs against pathogenic oral bacteria and specific phases of RA development. Results: The four groups each included 51 FDRs balanced for potential confounding factors of periodontitis. Median age was 51 years (IQR: 39 – 60), 70% were women, 27% smokers. Although quantitative differences existed between the four groups of probands, none of the IgG against the periodontal pathogens differed significantly between the groups. Furthermore, IgG levels against P. gingivalis were not associated with seropositivity (ACPA or RF) (p=0.90), age (P=0.15), shared epitope status (p=0.63) or sex (P=0.26). Conclusions: Longitudinal studies are still needed to establish the causal involvement of periodontitis, or its associated bacteria, on RA development. However, the results from this case-control study do not suggest that circulating antibody levels against common periodontal pathogens are associated with specific phases of RA development and useful as a prognostic tool. References: Ann Rheum Dis 2012;71:638-641 Disclosure of Interest: None declared